Réponses

2013-11-02T09:56:24+01:00
a = 5/3 - 3/2 + 1 - 7/6 - 1/5
= 10/6 - 9/6 
+ 1 - 7/6 - 1/5
= 1/6 + 1 - 7/6 - 1/5
= 7/6 - 7/6 - 1/5
=-1/5

b = -5/6 : (-7/2)
= -5/6 x (-2/7)
= 10/42
= 5/21

C = -30/21 : (-45/14)
= -30/21 x (-14/45)
= 420/945
= 4/9

D = 2/35 -1/7 +11/4
= 2/35 - 5/35 + 11/4
= -3/35 + 11/4
= 373/140

E = 5/4 x 12/35
= 60/140
= 3/7

F = (5/7 - 1/3 ) x ( 1/4 + 3/2 ) 
= ( 15/21 - 7/21 ) x ( 2/8 + 12/8 )
= 8/21 x 14/8
= 112/168
= 2/3

G = 3 - 2/3 x 5-2 / 8-2
= 3 - 2/3 x 3/6
= 3 - 6/18
= 8/3

h = (-6/7 : 9/14) x (-3) + 5 
= ( -6/7 x 14/9 ) x (-3) + 5
= -84/63 x (-3) + 5
= 4 + 5
= 9